(untitled) (New Delhi, 1994)
Kavita 93, a collection from contemporary Indian poetry. KAVITA 93 A ... Select a special feature you wish ... manual of your choice online.
Keywords: Thơ Ấn Độ,Indic poetry; Dịch sang tiếng Anh,Translations into English; Thế kỷ 20,20th century